“Hills of Activity” as an effective method for mitigating ground surface vibration in sustainable residential development - Aneta Herbut (PLoS ONE, 2025)
This paper investigates the vibration mitigation efficiency of a hill and a system of hills. The effects of obstacle height, slope inclination angle, the number of embankments used, and their shape on vibration reduction levels are analyzed. It has been observed that larger, flatter hills reduce the dominant vertical velocity component more effectively than smaller, steeper ones. Multiple rows of obstacles can be employed to improve vibration reduction. The effectiveness of the solution was examined for both low-frequency (20 Hz) and high-frequency (60 Hz) excitations. The vertical component of the velocity vector may be reduced to as low as 30% of its initial value due to the application of the hill(s) or row(s) of hills. The main advantage of the proposed solution, in the form of a convex soil obstacle, is that it reduces both vibrations and noise (factors that often co-occur). Moreover, the system of hills can also function as playgrounds, providing a recreational space for children. Classical concave barriers (such as commonly used open trenches) do not offer such benefits. The proposed solution aligns with an important research direction in sustainable residential development.